‘It’s the end of the world as we know it and I feel fine - Sheth, Nandita Baxi (Visual inquiry, 2022)
Just as R.E.M.’s lead singer Michael Stipe repeats, ‘It’s the end of the world as we know it and I feel fine’, this article adopts a cautiously hopeful attitude towards ends as paradigmatic shifts away from colonial, ordered and fixed ways of understanding the world. Some ends are not destructions, conclusions or stagnations; but are alternatives from ‘the world as we know it’, which is both desirable and ‘fine’. On the other hand, some ends, such as species extinction, are devastatingly final. Historical, cultural, biological and technological ends are encapsulated in two works of art created more than 500 years apart: German printmaker Albrecht Dürer’s 1515 woodcut print Rhinoceros and British artist Alexandra Daisy Ginsberg’s 2018 video installation The Substitute. These two renderings traverse a range of moments from the rhinoceros first entering western European visual culture to the extinction event of one rhinoceros subspecies. Philosophical themes emerging from these works are explored through Franz Fanon’s articulation of the colonial subject, Jacques Derrida’s ideas on invention and Georges Didi-Huberman’s firefly image. Fanon, Derrida and Didi-Huberman call for radical change in which ends are necessary to projects of liberation and interconnectedness.